THE CONCEPT OF UTILITARIANISM IN THE SHORT STORY “THE ONES WHO WALK AWAY FROM OMELAS” IN “THE WIND'S TWELVE QUARTERS” BY URSULA KROEBER LE GUIN - Siti Nurrohmah Azizah; Mahi M. Hikmat (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2023)
This study examines the concept of utilitarianism presented in the short story "The Ones Who Walk Away from Omelas" in "The Wind's Twelve Quarter" by Ursula K. Le Guin. Through an ethical approach in sociology literature, this study aims to analyze the ethical implications of collective action in achieving general happiness in Omelas. Through analysis of the sociology of literature, this study reveals the social practices of utilitarianism presented in the story. In utilitarianism through ethical theory developed by philosophers Jeremy Bentham and John Stuart Mill, argues that a good action is an action that produces as much happiness as possible for as many people as possible. In the context of this short story, society has collectively chosen to maintain general happiness by ignoring the fate of the oppressed individual. This raises deep ethical questions about the justice and morality of emotional action. This study also analyzes the attitudes of individuals who choose to leave Omelas. This action shows disapproval of the principle of utilitarianism which sacrifices one individual for the sake of broad happiness. The attitude of individuals who dare to walk raises ethical overtones about our responsibilities to society and individuals. Through an analysis of ethical theory in a literary sociology approach, this study concludes that "The Ones Who Walk Away from Omelas" pushes to limit the ethical boundaries of utilitarianism and change moral compromises in achieving peace. The social and psychological implications of this story awaken our awareness of the moral dilemmas associated with emotional action and raise deep ethical questions about human values ​​and justice. Keywords: Utilitarianism, Sociology of Literature, Ethics